VALUE CO-CREATION MODEL: IDENTIFYING CULTURAL RESOURCES FOR BAIJIU TOURISM IN BOZHOU, CHINA - Han , Xue; Tangit, Tania Maria; Mogindol, Spencer Hedley; Suffian, Mohd Firdausi; Chong , Pit Kee (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study intends to explore the value co-creation model in identifying cultural resources for emerging tourism niche, Baijiu tourism in China. However, according to the data statistics of the Bureau of Culture, Tourism and Sports of Bozhou City in Anhui region, since 2020, the number of tourists visiting Bozhou has shown a downward trend, and the revenue is also not optimistic. the concept of cultural tourism resource development in Bozhou city is still relatively conservative. The tourist attractions in the city are still mainly shallow sightseeing tourism, lacking a hierarchical model system. This study explores the role of multi destination stakeholders in collaborating with each other to create values for the Baijiu tourism industry in Bozhou city. This is a qualitative explorative study, and data are collected through 20 participants in semi-structured interviews and participation observations. The study found that various stakeholders in Baijiu tourism, including tourists, Baijiu consumers, Baijiu enterprises, government and local community, made significant contributions through their collaboration in preserving cultural heritage in identifying those resources for Bozhou city, a city with rich historical background and important cultural sites. Suitable tangible and intangible type of cultural resources related to Baijiu tourism had been identified by stakeholders. Besides that, by identifying the cultural resources, the collaboration between various destination stakeholders with one another could create a cultural heritage framework and has a great potential in promoting Bozhou city as Baijiu tourism hub. The study concludes with the idea that stakeholders’ mechanisms could also create a brand output value to enhance Baijiu tourism industry. It recommends Baijiu tourism can be further enhanced by considering the China’s rating system for tourist destinations to achieve excellent 5A rating level for cultural resources identified in Bozhou.